2001
DOI: 10.1093/gerona/56.9.m589
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Stability During Forward-Induced Stepping for Dynamic Balance Recovery in Young and Older Adults

Abstract: During forward-induced protective stepping, otherwise healthy older adults who had experienced falls showed particular differences in their control of lateral body motion that were not attributable to changes in anticipatory postural mechanisms. Aging changes in controlling lateral body motion during protective stepping appear to involve factors that intervene between the first-step liftoff and foot contact and/or adaptations in stepping patterns related to prior planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 27 publications
6
97
0
Order By: Relevance
“…This review has shown that balance evaluations are very different, both in protocols and in measurement methods, and that direct comparisons among studies and data interpretation are extremely limited. Many experimental protocols indicated that increased postural sway in older adults is well documented and research findings highlighted a correlation between postural sway and increased risk of falling not only on a static board (Baloh et al 1994;Benjuya et al 2004;Billot et al 2010;Fernie et al 1982;Hasselkus & Shambes 1975;Kang et al 2009;Lajoie et al 2002;Lord et al 1994;Maki et al 1994;Melzer et al 2004;Stel et al 2003), but also on an unstable board (Nardone et al 1994;Nardone et al 2000;Woollacott & Shumway-Cook 1990;Wolfson et al 1994;Rogers et al 2001). All Medial lateral sway in both the conditions (eyes open and closed) was found to be a distinguishing variable between older "fallers" and "non-fallers" in both static and dynamic narrow stance condition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review has shown that balance evaluations are very different, both in protocols and in measurement methods, and that direct comparisons among studies and data interpretation are extremely limited. Many experimental protocols indicated that increased postural sway in older adults is well documented and research findings highlighted a correlation between postural sway and increased risk of falling not only on a static board (Baloh et al 1994;Benjuya et al 2004;Billot et al 2010;Fernie et al 1982;Hasselkus & Shambes 1975;Kang et al 2009;Lajoie et al 2002;Lord et al 1994;Maki et al 1994;Melzer et al 2004;Stel et al 2003), but also on an unstable board (Nardone et al 1994;Nardone et al 2000;Woollacott & Shumway-Cook 1990;Wolfson et al 1994;Rogers et al 2001). All Medial lateral sway in both the conditions (eyes open and closed) was found to be a distinguishing variable between older "fallers" and "non-fallers" in both static and dynamic narrow stance condition .…”
Section: Discussionmentioning
confidence: 99%
“…Thus the loss of lateral postural control in fallers could be explained by an asymmetric muscle strength loss in their lower limbs. Good lateral postural control is essential for a protective role in response to destabilizing events (Rogers et al 2001).…”
Section: Distinguishing Characteristics Of Older "Fallers" and "Non-fmentioning
confidence: 99%
“…Failed compensatory steps have been observed in 45% of older adult falls in the free-living environment [17]. Although compensatory stepping is impaired with older age [13,24,26,33,39], it is a modifiable skill that improves with practice [4,11,40,46]. A task-specific fall prevention training program has been developed based on compensatory step training that has successfully reduced trip-related falls by the elderly after laboratory-induced trips [11] and prospectively reported trip-related falls that occur in the community [41].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, reduced toe clearance may also be related to the significant reduction in mediolateral (ML) center of mass (COM)-center of pressure (COP) separation determined for older adults, which results in reduction in sideways momentum of the body 22) . Without adequate sideways momentum of the body more energy would have been required to lift the swing leg sufficiently to clear the obstacle edge, because elevation of the swing leg occurs with a sideways tilting motion of the body 23) . Older adults appeared to adopt a stability-oriented strategy to minimize the risk of ML instability by reducing toe clearance of the trailing leg.…”
Section: Discussionmentioning
confidence: 99%